2021
DOI: 10.21608/aimj.2021.100730.1604
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cardiac Functions in Neonatal Sepsis

Abstract: Background: One of the major organs influenced in neonatal sepsis is the heart. Echocardiogram gives real-time data on the cardiovascular execution instead of reliance on the clinical signs alone. Aim of the work: to study the role of transthoracic echocardiogram in the assessment of systolic and diastolic cardiac functions in septic neonates. Patients and methods: This cross sectional study was carried out on 80 neonate subdivided into 4 groups (septic full-term, septic preterm, nonseptic full-term and non-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 5 publications
(8 reference statements)
3
2
0
Order By: Relevance
“…According to tissue Doppler analysis, the right ventricle's diastolic function represented by the tricuspid E/A ratio, was found to be considerably poorer in the examined neonates with sepsis than in the aseptic group indicating right ventricular diastolic dysfunction. This is consistent with the study by Abdel Hakeem et al which showed that the tricuspid E/A ratio was lower in cases than in control (25) .…”
Section: Regardingsupporting
confidence: 93%
See 4 more Smart Citations
“…According to tissue Doppler analysis, the right ventricle's diastolic function represented by the tricuspid E/A ratio, was found to be considerably poorer in the examined neonates with sepsis than in the aseptic group indicating right ventricular diastolic dysfunction. This is consistent with the study by Abdel Hakeem et al which showed that the tricuspid E/A ratio was lower in cases than in control (25) .…”
Section: Regardingsupporting
confidence: 93%
“…Also, septic patients' group had higher left atrial diameter compared to healthy group. Additionally, Abdel Hakeem et al revealed that the septic group had greater pulmonary artery pressure than the healthy group, validating our findings (25) .…”
Section: Regardingsupporting
confidence: 90%
See 3 more Smart Citations